Strength training and sarcopenia—a mandatory link: focus on MicroRNAs - Cione, Erika; Abrego-Guandique, Diana Marisol; Chiari, Aldo; Cannataro, Roberto (Frontiers in Aging, 2025)
Over the last 20 years, increased life expectancy has been observed in men and women, resulting in a rise in the prevalence of diseases among the aging population. From this, sarcopenia has an estimated prevalence of 10%–16% of older people worldwide. Losing strength and muscle mass in the 65–70 age group represents a significant public health problem. In this review, we emphasize the essential importance of strength training in managing sarcopenia, highlighting the role of microRNAs, small nucleotides that were the subject of last year’s Nobel Prize in Physiology or Medicine. These microRNAs regulate protein synthesis and are present in all biological fluids. Some of them are expressed differently by subjects affected by sarcopenia (as happens in various forms of cancer or other diseases). Therefore, monitoring a specific signature of microRNAs can better clarify the etiopathology of sarcopenia, providing an early biomarker for sarcopenia (currently, there are some hypotheses, but none is well recognized), and even serve as the basis for the development of drugs.